2010
DOI: 10.1007/s00405-010-1398-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus percutaneous tracheostomy: an evidence-based approach

Abstract: The choice between surgical (ST) and percutaneous tracheostomy (PT) is not often based on evidence. The aim is to evaluate the quality of evidence in published articles comparing the two methods. A MEDLINE search was done. From 298 articles found, 37 fulfilled the inclusion criteria and 35 were further analyzed. No study was based on type I evidence, 13 (37%) represented type II, in 1 (3%) a clear-cut definition between type II or III was not possible and 21 (60%) represented type III or IV evidence. Taking in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
1
14
1
3
Order By: Relevance
“…Although more studies favored percutaneous tracheostomy, they are often based on studies with a lower level of evidence. 15 Our data showed a slightly higher mortality rate for patients who underwent percutaneous tracheostomy, which is not consistent with multiple systematic reviews and meta-analyses. This could be due to the large sample size used in this study, as these differences may be statistically significant but may not be clinically significant.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Although more studies favored percutaneous tracheostomy, they are often based on studies with a lower level of evidence. 15 Our data showed a slightly higher mortality rate for patients who underwent percutaneous tracheostomy, which is not consistent with multiple systematic reviews and meta-analyses. This could be due to the large sample size used in this study, as these differences may be statistically significant but may not be clinically significant.…”
Section: Discussioncontrasting
confidence: 74%
“…In a review of available studies to evaluate the quality of evidence in the literature, Pappas et al confirmed that recommendations are controversial. Although more studies favored percutaneous tracheostomy, they are often based on studies with a lower level of evidence …”
Section: Discussionmentioning
confidence: 99%
“…In our study, the renal failure rate was significantly higher in the mortality group compared to the surviving group (p<0.05) ( Table 2). Tracheostomy is a surgical method frequently applied to patients with long term mechanical ventilation, for treatment of upper respiratory tract obstruction, and those with endotracheal intubation in ICU and predicted to remain linked to a mechanical ventilator for a long period (27,28). Percutaneous tracheostomy (PT) is easily performed, has low complication rates and can be performed in a short period at the patient's bedside so it is mostly chosen in recent years and is frequently used in the ICU for cases with elective tracheostomy especially (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions, in fact, cannot be accepted, for different reasons such as small sample size, lack of randomization of the patients, lack of randomization for the procedure, biased patient selection criteria, uneven operators-to-procedures ratio within the same team, lack of a single-team performance of both the procedures, no direct comparison between the techniques but indirect comparison with other studies. [40–45] The evidence brought on elective patients by teams experienced in both techniques with sound prospective randomized controlled trials (PRCTs) has however proved, as a matter of fact, a superiority of OST over PCT in elective scenarios (ICU, operating theater and bedside) in terms of overall safety and cost-effectiveness and in terms of perioperative and postoperative complications;[46] and an increased risk of delayed airway loss (more difficult cannula changes or inability to replace the cannula) in the PCT groups. [47] Indeed a major meta-analysis of elective studies had found much higher perioperative complications rate and mortality with PCT than with OST, which appeared to have more minor problems related to postoperative wounds.…”
Section: Recommendations On Which Esa To Use In Critical Airway Scenamentioning
confidence: 99%